Under the oak tree, volume 1 eaudiobook A novel. - Kim, Suji (Under the Oak Tree--Novel, 2024)
NEW YORK TIMES BESTSELLER • Most fairytales end with a wedding and a happily-ever-after—but this is no fairytale. The updated and official translation of Under the Oak Tree , the #1 webnovel on MANTA. “Currently the most popular romantasy webnovel . . . Under the Oak Tree is a Korean romantasy with intense emotional depth, weaving trauma and love in a medieval setting. [It] explores the internal and external struggles of Lady Maximillian and Sir Riftan in a fraught, evolving marriage.”—Bleeding Cool, in praise of Under the Oak Tree (The Comic) Lady Maximilian is the daughter of the powerful Duke Croyso, but she is rarely allowed outside her family’s sprawling castle for fear that her stutter will tarnish their noble name. When she is forced to marry Sir Riftan, a lowborn knight caught in one of her father’s schemes, Maxi doesn’t dare hope for happiness, let alone love. Her stumbling communication and his gruff manner sour their relationship before it can begin, and Riftan leaves without a word the morning after their vows are exchanged. Now, three years after their disastrous wedding night, Riftan has returned as a war hero. To Maxi’s surprise, despite rumors that he was offered marriage to Princess Agnes, a beautiful and renowned sorceress, Riftan still wants Maxi for his wife. And when he comes to claim her, his longing becomes a desire that bewilders Maxi, even as she is overcome by the scorching heat that Riftan’s presence ignites within her. As she learns to navigate the intricacies of her new life, Maxi will find herself and her courage, and discover that she is anything but powerless. This volume collects chapters 1-76 of the original webnovel by Suji Kim.